Implikasi Kebijakan Affirmative Action dalam Penentuan Quota Wanita Sebagai Calon Anggota Dewan Perwakilan Rakyat dalam Perwujudan Kesetaraan Gender di Indonesia - Anak Agung Dita Intan Pertiwi; I Nyoman Putu Budiartha; Diah Gayatri Sudibya (Warmadewa Press, 2022)
The affirmative action policy of determining the quota of women as candidates for members of the DPR regulates the relationship between women in the involvement of legislative candidates, not from the seats of women's representation. The purpose of this study is to find out the practical political arrangements as members of the DPR through elections. Knowing the position of women in practical politics in council members through elections as a manifestation of Affirmative Action policies in Indonesia. This research uses normative legal research. The collection technique is an inventory, analysis with a statutory and theoretical approach. The results of the study indicate that the regulation of practical politics for members of the People's Representative Council (DPR) through general elections is regulated in Law no. 7/2017which requires political parties to assign at least 30% of female legislative candidates to contest in the legislative elections. The position of women in practical politics as members of the council through elections as the embodiment of Affirmative Action policies in Indonesia, has an important role to participate in, but in the general election contestation in Indonesia it is still descriptive, namely only to fulfill administrative requirements.